Prevalence, awareness, treatment, and control of hypertension: Rule of thirds in the Skaraborg project - Lindblad, Ulf (Informa Healthcare, 2012)
OBJECTIVE: To describe the prevalence, awareness, and control of hypertension in a Swedish population during the early 2000s to address implications for care and prevention. DESIGN: A cross-sectional population survey. SETTING: Primary health care in Skaraborg, a rural part of western Sweden. SUBJECTS: Participants (n =2816) in a population survey of a random sample of men and women between 30 and 75 years of age in the municipalities of Vara (81% participation rate) and Skövde (70%), in western Sweden during 2001–2005. MAIN OUTCOME MEASURES: Anthropometric measures, blood pressure, leisure-time physical activity, current smoking, fasting glucose, and cholesterol. Hypertension was defined as ongoing treatment for hypertension, or three consecutive blood pressure readings ≥140 systolic and/or ≥90 mmHg diastolic. Hypertension was considered controlled when the blood pressure was <140/90 mm Hg (both). RESULTS: The prevalence of hypertension was 20% in both men and women with a steep increase by age. Among hypertensive subjects, 33% were unaware, 36% aware but uncontrolled, and 31% aware and controlled, with no statistically significant differences between men and women. Patients with diabetes had a higher awareness (87% vs. 64%, p <0.001), but the same control rate (56% vs. 44%, p =0.133), when compared with those without diabetes. CONCLUSION: A large proportion of subjects with hypertension are still unaware of their condition, or aware but not controlled. It is important to emphasize population-based prevention to reduce the prevalence of hypertension, to perform screening to increase awareness, and to improve implementation of expert guidelines in clinical practice to improve control.